2020
DOI: 10.1016/j.nima.2020.163507
|View full text |Cite
|
Sign up to set email alerts
|

Rossi-alpha measurements of fast plutonium metal assemblies using organic scintillators

Abstract: In this work, Rossi-alpha measurements were simultaneously performed with a 3 He-based detection system and an organic scintillator-based detection system. The assembly is 15 kg of plutonium (93 wt% 239 Pu) reflected by copper and moderated by lead. The goal of Rossi-alpha measurements is to estimate the prompt neutron decay constant, alpha. Simulations estimate k eff = 0.624 and α = 52.3 ± 2.5 ns for the measured assembly. The organic scintillator system estimated α = 47.4 ± 2.0 ns, having a 9.37% error (thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Stilbene is known to exhibit highefficiency light emission properties but has poor photostability. 36,37 This stilbene derivative was then used as the organic cation for the formation of novel RInBr 4 , which is, to the best of our knowledge, one of the few known pseudoternary hybrid organic−inorganic indium(III) halides to date. The novel compound was structurally characterized using X-ray diffraction methods.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stilbene is known to exhibit highefficiency light emission properties but has poor photostability. 36,37 This stilbene derivative was then used as the organic cation for the formation of novel RInBr 4 , which is, to the best of our knowledge, one of the few known pseudoternary hybrid organic−inorganic indium(III) halides to date. The novel compound was structurally characterized using X-ray diffraction methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, an alternative approach has been taken, wherein a previously known efficient light emitter, stilbene, has been modified in a novel fashion by adding a trimethylated ammonium group to one of the two phenyl rings. Stilbene is known to exhibit high-efficiency light emission properties but has poor photostability. , This stilbene derivative was then used as the organic cation for the formation of novel RInBr 4 , which is, to the best of our knowledge, one of the few known pseudoternary hybrid organic–inorganic indium­(III) halides to date. The novel compound was structurally characterized using X-ray diffraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on the nonrandom distribution between neutron detection times: the population of correlated prompt neutrons (those from the same fission chain seed) decays exponentially as fission chains extinguish [15]. Experimental results showed that the decay is modeled better by a two-exponential function than a one-exponential function when the assembly of fissile material is reflected [16,6], the model was theoretically derived from two-region point kinetics [17,18,11], and validated with a combination of experiments and simulations [12,19]. The two-exponential Rossi-alpha probability density function for reflected assemblies p R (τ) is given by…”
Section: Rossi-alpha Methodsmentioning
confidence: 99%
“…The detection system is identical to that of Refs. [19,12], which contain further details. A second OSCAR and two Neutron Multiplicity 3 He Array Detectors (NoMADs -15 3 He tubes embedded in a high-density polyethylene matrix [29]) were also present, all 47 cm from the center of the assembly, but data obtained from these systems are not used in this work.…”
Section: Methodsmentioning
confidence: 99%
“…[8]). The OSCAR prototype comprises 12, 5.08 cm × 5.08 cm diameter transstilbene crystals coupled to photomultiplier tubes [9,10,11], suspended in powder-coated iron wire meshes and held in place with porous polyurethane foam [12]. The detectors are powered with high voltage and pulses are digitized with a CAEN v1730 waveform digitizer (16 channels, 500-MHz sampling rate, 14-bit resolution, 2-V dynamic range).…”
Section: Measurement Specificationsmentioning
confidence: 99%